First report of blaOXA-48 producing Klebsiella pneumoniae isolates from wastewater in Morocco - Amine Aiddi; Ilham Zerdani; Aboubakr Khazaz; Ihssane Benzaarate; Hafsa Mguild; Fatna Bourjilat; Kaotar Nayme (AOSIS, 2024)
No abstract available.